2018
DOI: 10.11118/actaun201866010155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bean Cultivars on Soil Microorganisms

Abstract: The aim of this study was to determine the microbiological activity in soil under beans in organic and conventional production. Organic production was conducted on the field in the village Pivnice (Serbia), while conventional production was conducted in the village Curug (Serbia) during 2014 on the chernosem type soil. Cultivars of beans Belko, Dvadesetica, Maksa, Slavonac, Sremac, Zlatko were used. Before sowing, the bean seeds were inoculated by biofertilizers NS-Nitragin. NS-Nitragin contains a mixture of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…Different plant species can influence microbiome composition and structure, and some species appear to have a much stronger association with specific microbes than others [ 19 , 20 ]. The effects of plant genotype on the rhizobiome have been reported in Arabidopsis , cucumber, bean, Brachypodium , maize, barley, and wheat [ 21 – 26 ], though the intra-specific genetic contribution to microbiome assembly is relatively low. Decades of research have shown that plant genotype/species and developmental stages impact the qualitative and quantitative composition of plant root exudates [ 21 , 27 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different plant species can influence microbiome composition and structure, and some species appear to have a much stronger association with specific microbes than others [ 19 , 20 ]. The effects of plant genotype on the rhizobiome have been reported in Arabidopsis , cucumber, bean, Brachypodium , maize, barley, and wheat [ 21 – 26 ], though the intra-specific genetic contribution to microbiome assembly is relatively low. Decades of research have shown that plant genotype/species and developmental stages impact the qualitative and quantitative composition of plant root exudates [ 21 , 27 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even in conditions when abiotic processes lead to the dominant loss of organic mass, oxidation to CO2 and other inorganic molecules is mainly the result of the activity of organisms in the soil. Decomposition organisms consist of a complex community of soil biota, including soil microflora and fauna [62]. Fungi and bacteria are ultimately responsible for the biochemical processes of decomposition of organic residues [63].…”
Section: Edaphic Factorsmentioning
confidence: 99%
“…In recent years, people's awareness of the importance of soil quality from the ecological aspect [6] and the production of cultivated plants has increased, which has led to renewed interest in harvest residues (HR), green manure and other organic fertilizers as sources of SOM and nutrients for cultivated plants [1]. The aim Pržulj, N. et al: Significance of harvest ...... Archives for Technical Sciences 2022, 26(1), [61][62][63][64][65][66][67][68][69][70] Technical Institute Bijeljina, Archives for Technical Sciences. Year XIV -N 0 26. of this paper is to present literature data on the importance of HR and their decomposition in maintaining the quality of arable land in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Дослідженнями встановлено, що значний вплив на мікробіологічну активність чорноземних ґрунтів мають система удобрення сільськогосподарських культур, обробіток ґрунту, ланки сівозмін, насичення сівозмін просапними і зерновими культурами [2][3][4][5][6].…”
Section: вступunclassified